Hubungan Pengetahuan Anggota Keluarga dengan Kualitas Hidup Klien Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Sumbersari Kabupaten Jember - Ana Karunia (Fakultas Keperawatan, 2025)
Background: Family structure significantly influences the implementation of family functions, including healthcare. In Indonesia, awareness and understanding of family functions in diabetes care remain low (29.5%), potentially impacting the quality of life for diabetic clients. This study aimed to analyze the relationship between family knowledge and the quality of life of type 2 diabetes mellitus (DM) clients. Methods: This analytical observational study employed a cross-sectional approach. The study population comprised type 2 DM clients from the Sumbersari Health Center Working Area in Jember, East Java, Indonesia, with a sample of 98 clients selected using stratified random sampling. Data were collected in 2024 using a client characteristics questionnaire, the Diabetes Knowledge Questionnaire 24 (DKQ-24), and the Diabetes Quality of Life (DQOL) scale. Results: Chi-square test results revealed a significant relationship between family knowledge and client quality of life (p=0.019; Cramer's V=0.238; OR=2.750; 95% CI= 1.171−6.457). This indicates that lower family knowledge is associated with a significantly decreased quality of life among DM clients. Conclusion: Family knowledge plays a crucial role in the quality of life of DM clients. These findings underscore the importance of targeted educational interventions to improve family knowledge regarding diabetes management, which could lead to substantial improvements in the quality of life for individuals with type 2 DM.
Entry oleh Arif 2026 Februari 09
Keywords: Family Function; Diabetes Knowledge; Diabetes Quality of Life